Service Quality, Sharia Compliance, and Patient Loyalty: The Mediating Role of Patient Satisfaction in Islamic Hospitals - Nanda Suryadi; Identiti Identiti; Arie Yusnellly (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine Patient Satisfaction Mediating the Effect of Service Quality and Hospital Sharia Compliance on Patient Loyalty atSharia Hospitals in Riau Province in an Islamic Perspective. The type of research used in this research is quantitative research. The sample useduses random sampling techniques where sample withdrawal occurs randomly, namely making samples when meeting with anyone whenconducting research with a sample size of 400 respondents. The data analysis technique used in this study is to use the Partial Least Square(PLS) approach with SmartPLS 4 software tools to test the relationship between variables. The results obtained in this study show that servicequality has a positive and significant effect on patient satisfaction at Islamic hospitals in Pekanbaru city, hospital Sharia compliance has apositive and significant effect on loyalty at Islamic hospitals in Pekanbaru City, Service Quality has no significant effect on Sharia HospitalPatient Loyalty in Pekanbaru  city,  Sharia  Compliance  has  a  positive  and  significant  effect  on  patient satisfaction at Islamic hospitals in Pekanbaru city, Significant Effect Satisfaction can mediate service quality on patient loyalty at Islamic hospitals in Pekanbaru city, significanteffect Satisfaction  can  mediate  sharia  compliance  on  patient  loyalty  at  Islamic  hospitals, Satisfaction has a positive and significant effecton loyalty at Islamic hospitals in pekanbaru city.